Timing decisions of housing sales and development based on real option theory - Zhang, Ling; Shi, Dingyin; Chang, Xin; Wen, Haizhen (International Journal of Strategic Property Management, 2021)
Based on the real option theory, this paper studies the impact of uncertainty on the timing decisions required in housing development and sales. Data of newly-built houses and corresponding plots in Hangzhou, China, are used for empirical analysis. In order to better reflect the changes in market demand under frequent policy intervention, in addition to the usual price volatility, this paper introduces the volatility of trading volume to measure the uncertainty of China’s real estate market. The results show that the volatility of trading volume has a significant impact on timing decisions. Also, trading volume volatility can better reflect the characteristic of deferred option than can price volatility, especially during the sales phase. This study provides evidence to support Bar-Ilan and Strange’s (1998) research of sequential investment. Because of the existence of the second option, i.e., sales timing, the starts in the first stage are not too sensitive to uncertainty. In the case of the second option, the longer the construction period is, and the lower the cost of the first stage is, the higher will be the probability of triggering the start. In addition, the characteristics of market risk aversion are obvious in the study area, especially in the suburban area. First published online 29 December 2020